Effect of EGR strategy on combustion and emission of DMDF engine for meeting China VI emission legislation. (1st September 2021) - Qu, Guofan; Yao, Anren; Chen, Chao; Ren, Jiachao; Yao, Chunde
Highlights: Bouble loop (DL) EGR mode contains both low pressure EGR and high pressure EGR were use. DMDF engine with DL EGR could meet the NOx requirements of China VI emission legislation. DMDF engine with DL EGR meeting demand of China VI do not the help of SCR system. Abstract: Study on EGR mode and demand were carried out to meet with the requirements of main emission limits of China VI on a diesel methanol dual fuel (DMDF) engine equipped with Hybrid exhaust gas recirculation (EGR) system coupled with back pressure valve (BPV). According to the World Harmonized Steady-State Cycle (WHSC) test cycle, the effects of EGR mode under high methanol energy ratio (MER) on the combustion, emissions and economy of DMDF engines were studied without the help of selected catalyst reduction (SCR). Considering the weight based on WHSC test cycle of full load was only 0.083, and EGR demand of full load was low, the optimal EGR strategy under different loads except full load was determined for DMDF engine. The results demonstrated that through the early injection strategy with high MER, particulate matter (PM) emissions were all at an extremely low level, far below the requirements by legislation limit of 0.01 g/kWh. With the increase of EGR rate, nitrogen oxides (NOx) emissions were significantly reduced under different loads, accompanying with one or more EGR modes at 25%, 50%, and 70% loads to ensure that NOx emission could meet the requirements by legislation limit of 0.4 g/kWh, while PM emissions were at a very low level at the same time. Demand for EGR rate of light loads was generally higher than that for medium loads, but under light loads, each of hybrid EGR modes could meet the demand of China VI legislation. While under medium loads, the dual loop (DL) EGR modes, i.e., both low pressure (LP) and high pressure (HP) EGR mode must be needed. In LP EGR mode combined with back pressure valve (BPV), higher EGR rate was required under the same NOx control target, owing to the higher intake air volume than those of other modes. The trade-off relationship in HP_BPV mode between NOx and PM emissions still existed, and high EGR rate often leaded to an increase in PM.